An Investigation of the Fe-Mn-Si System for Li-Ion Battery Negative Electrodes. Issue 2 (1st January 2019) - Cao, Yidan; Scott, Benjamin; Dunlap, R.A.; Wang, Jun; Obrovac, M. N.
Abstract : Fe-Mn-Si alloys prepared by ball milling were investigated as negative electrodes for Li-ion batteries. X-ray diffraction and room temperature 57 Fe Mössbauer measurements were used to characterize alloy structure, which revealed the formation of ternary (Fe, Mn, )11 Si19 solid solutions. During cycling in Li cells, the formation of crystalline Li15 Si4 was effectively suppressed by inactive transition metal silicide phases, resulting in good cycling performance. In addition, Fe was found to be superior to Mn in avoiding excessive side reactions with electrolyte during cycling.